Highly-ordered nanoporous anodic aluminum oxide films - Voloshko, A.V.; Danilina, V.V.; Mateychenko, P.V.; Bespalova, I.I. (Functional Materials, 2012)
The samples of the nanostructured aluminum oxide films were obtained by anodic oxidation method (thickness is near 100 μm and dpores = 42+4 nm). Two stage aluminum oxidation was carried out in a two electrode electrochemical cell at 0°C and the voltage value of 40 V. Oxalic acid solution was used as an electrolyte. The optimal heat treatment conditions, of the weak luminescent films without destruction of the order structure have been proposed.